National Service for Health : the Labour Party's post-war policy (London : Labour Party)
1943-04 1943 1940s 24 pages Local Health Centres In each divisional area there should be four or more Local Health Centres, each linked with the Divisional Health Centre, and each served by from eight to twelve general practitioners. In rural areas, these Local Health Centres may have to be much more numerous in proportion to the population, and may have a much smaller number of doctors — perhaps only one or two. At these Centres patients would obtain the service of their home doctor ; and through him they could draw upon a complete service of specialists at, or from, the Divisional Centre or Hospital. The Local Health Centres would also organise the services of midwives, home nurses, home helps, health visitors, and social welfare workers. Health Records One of the great advantages of a unified medical service, with Health Centres as proposed, would be that complete records of the health of all the people could be kept. The Health Centres, Local and Divisional, should have an appropriate clerical staff; and the clerical work should include the keeping of health records. The records would be available, in strict confidence, to all doctors in the unit who may require them, and would be sent to the Health Centre of any other area to which the individual may move. The value of such continuous recording of the medical history of each individual, in health and in sickness, need hardly be emphasised. Suppose, for instance, that a boy is examined in the school medical inspection. Is it not obvious that the record of that inspection should be available in confidence to the doctor who may afterwards see the boy at the Health Centre, or at home? Presently, the boy may go away to some other part of the country, and may there need a doctor's attention. Would it not be sensible that that doctor should have access, without difficulty, to the boy's medical history? If the boy had to go into hospital, would it not be useful that the doctor in charge during convalescence should have knowledge of the record of his case whilst in hospital and before he went there? Only an organised, unified Medical Service, with an adequate clerical staff, can provide such a system of records. Specialist Services One of the developments most needed to make the nation's Medical Service comprehensive is the provision of a service of specialists, available to all who need it. The plan outlined above will afford by far the best means of organising such a Service. (Some Local Authorities now find it convenient and economical to employ full-time specialists, who divide their time between the clinics and the municipal hospitals. The existing law allows a local doctor to call in a specialist to a patient's home, charging the cost to the Local Authority ; but this applies only to maternity cases.) Home Doctors The general practitioner, or "home doctor," is the first line of the nation's health defences; and he must always retain that position. The confidential relation between doctor and patient is an indispensable part of a satisfactory health service. It is becoming apparent, however, that the present system of organising and paying for the doctors' services has become increasingly unsatisfactory from the standpoint of the nation, of the patient, and of the doctor himself. The patient is not getting a service that is preventive, comprehensive, open to all, and fully efficient. In particular, the nation's resources of doctoring are ill distributed, and the doctor's conditions of employment do not adequately protect his own health, or his freedom as a guardian of health. 17 36/H24/40